An encyclopedic dictionary of indian languages literature - Kapoor A.N., Gupta V.P., Gupta Mohini and others (Radha Publishers, New Delhi, 2005)
Library Science
ENGLISH
Keywords: An encyclopedic dictionary of indian languages literature; Library Science; Library Science